2016
DOI: 10.1155/2016/5304028
|View full text |Cite
|
Sign up to set email alerts
|

The Microbiome of Animals: Implications for Conservation Biology

Abstract: In recent years the human microbiome has become a growing area of research and it is becoming clear that the microbiome of humans plays an important role for human health. Extensive research is now going into cataloging and annotating the functional role of the human microbiome. The ability to explore and describe the microbiome of any species has become possible due to new methods for sequencing. These techniques allow comprehensive surveys of the composition of the microbiome of nonmodel organisms of which r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
231
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(234 citation statements)
references
References 65 publications
2
231
0
1
Order By: Relevance
“…There have been calls recently for a better understanding of the role of gut microbiome in invasive species in general (Bahrndorff 2016) and in shaping phytophagous insect diversification and co-evolution with plants (Hammer and Bower 2015), yet few have stressed the significant breakthrough that "a gut microbiome invasiveness signature" in phytophagous insects would represent. In invasive species, dispersal ability, environmental tolerance, phenotypic plasticity and associated epigenetics are critical determinants of invasion success (Simberloff andRejmánek 2011, Chown et al 2015).…”
Section: Literature Supportmentioning
confidence: 99%
“…There have been calls recently for a better understanding of the role of gut microbiome in invasive species in general (Bahrndorff 2016) and in shaping phytophagous insect diversification and co-evolution with plants (Hammer and Bower 2015), yet few have stressed the significant breakthrough that "a gut microbiome invasiveness signature" in phytophagous insects would represent. In invasive species, dispersal ability, environmental tolerance, phenotypic plasticity and associated epigenetics are critical determinants of invasion success (Simberloff andRejmánek 2011, Chown et al 2015).…”
Section: Literature Supportmentioning
confidence: 99%
“…Many diseases (e.g., obesity, diabetes, and autistic disorder) are caused by specific gut microorganisms (Forslund et al, ; Kostic et al, ; Ley et al, ; Mulle, Sharp, & Cubells, ; Turnbaugh et al, ); therefore, a better understanding of the relationship between humans and the gut microbiome would be beneficial for human health and disease treatment. Beyond the application in the treatment of human disease, in recent years, some scientists have considered the application of the gut microbiome in the conservation of endangered animals (Bahrndorff, Alemu, Alemneh, & Lund Nielsen, ; Jiménez & Sommer, ; Redford, Segre, Salafsky, del Rio, & McAloose, ; Stumpf et al, ; Trevelline, Fontaine, Hartup, & Kohl, ; Wei et al, ; Yao, Xu, Lu, & Zhu, ). The scientists first propose the concept of conservation metagenomics, which is along with current methods, major scientific issues and significant implications in the study of host evolution, nutrition, physiology, and ecology and conservation (Wei et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The microbiota of insects can contribute to various aspects of host physiology, such as nutritional supplementation, tolerance to environmental perturbations, providing colonization resistance against pathogenic organisms, and priming the development and maturation of the host immune system [1,2]. It has thus been suggested that variation in the microbiota between individuals can explain differences in the phenotype, such as vector competency of vectors.…”
Section: Introductionmentioning
confidence: 99%